The Toronto Charter for Physical Activity: A Global Call for Action - Stelmach, Marian; Żbikowski, Jarosław; Wasilewska, Małgorzata (Polish Journal of Public Health, 2012)
In 2006 there the International Congress of Physical Activity and Public Health was held in Atlanta. Researchers and practitioners from around the world participating in that event agreed that there is the urgent need to undertake research on the role of physical activity in preventing diseases and there is a need to organize periodic congresses to present research results and exchange views in this area. The initiative met with great interest of researchers and the effect of that was a rapid progress in research in this field of science. During the Second International Congress of Physical Activity and Public Health in Amsterdam in 2008, there were presented the latest results related to the assessment of physical activity level, the recognition of sedentary behavior as distinct risk behaviors, as well as the role that various environments and policies play in forming human behavior. The same issues were major themes at the Third Congress of Physical Activity and Public Health in Toronto in 2010. The result of that congress was the adoption of the final document, which addresses the problem of lack of physical activity and the spread of sedentary lifestyle among all communities in the contemporary world. The papers discuss the essential bases and the process of ratification of that document as a basis for the promotion of physical activity in the different communities around the world. The document is called “The Toronto Charter for Physical Activity: A Global Call for Action”.